Connecting the dots: An interdisciplinary perspective on climate change effects on whales and whale watching in Skjálfandi Bay, Iceland. (1st July 2022) - Malinauskaite, Laura; Cook, David; Davíðsdóttir, Brynhildur; Karami, Mehdi Pasha; Koenigk, Torben; Kruschke, Tim; Ögmundardóttir, Helga; Rasmussen, Marianne
Abstract: The paper presents a synthesis of some of the interdisciplinary work from the ARCPATH project that focuses on the effects of climate change on Arctic social-ecological systems. It does so through the prism of whales and their recreational ecosystem services (ES). Whales present a group of species that are vulnerable to climate change and, at the same time, are central to the economies, cultures, and identities of many Arctic coastal communities. One such community is the town of Húsavík in Skjálfandi Bay, Iceland. The paper conducts an initial literature review to examine the effects of climate change on whales, globally, before using these findings and site-specific data from climate change modelling, whale observations from whale watching boats and whale watching trip records to investigate possible future impacts on whale watching in Skjálfandi Bay. The literature review identifies three categories of impacts on whales due to climate change, which concern changing distributions and migration, prey availability, and sea-ice and ocean temperature. Linear regression models identify statistically significant relationships between sea-surface temperatures (SST) and cetacean sightings for minke whales, blue whales and white-beaked-dolphins over the period 1995 to 2017. These species appear to have changed their usual feeding areas, and the results imply that further increases in SST are likely to further affect whale distributions. Future climate scenarios indicate that at least 2 °C of SST warming in Skjálfandi Bay up to 2050 might be inevitable regardless of the future emissions scenario, which implies nearly certain change that would require adaptation. The reliance of the local tourism sector on whale watching makes Húsavík vulnerable to the effects of climate change on whales. The results of this interdisciplinary inquiry emphasize the interconnectedness of different components of social-ecological systems and calls for adaptation planning that would enhance the resilience of local community to climate change and conservation measures that could enhance the protection of whales beyond the scope of the current whale sanctuary in Skjálfandi Bay.